KETERAMPILAN HIDUP YANG DIBUTUHKAN PEREMPUAN EKS NARAPIDANA UNTUK BERADAPTASI DI MASYARAKAT - Subroto, Mitro; Hakim, Rizky Fajrul (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: The ability to adapt in society is crucial for ex-prison women to reintegrate into their communities effectively. This study aims to identify the essential life skills required by these individuals to facilitate successful reintegration. The research employed a qualitative approach using semi-structured interviews with ex-prison women and community leaders. The findings indicate that essential life skills include emotional regulation, social support networks, vocational training, and mental health awareness. These skills are critical for building resilience and fostering positive relationships within their communities. However, the lack of access to resources and support services often hinders their ability to acquire these necessary skills. Therefore, this study emphasizes the need for comprehensive rehabilitation programs that address both psychological and social needs of ex-prison women. Keywords: Life Skills; Ex-Prisoner Women; Reintegration; Community Adaptation.